Perfil de policiais militares que apresentam estresse ocupacional - Menezes, Marcos Vinicius de Mendonça (2018)
The work of the military police generates stress both of an internal nature and of an external nature. These professionals carry out activities in constant contact with people, often involving an exhausting work, often being involved in unforeseeable situations of conflict, suffering and risk with their own life, from routine activities. It is a cross-sectional exploratory research, of quantitative character, with non-probabilistic sampling. The population of this study is the military police that develops the activities in the city of Aracaju. A minimum sample size of 176 participants will be used, with the sample error of 5% and the confidence level of 95%. To answer the objectives of this study, two questionnaires of different categories were applied. The first category, consisting of sociodemographic and occupational issues considered pertinent to the study, namely age, sex, marital status, occupation, professional category, length of service, psycho-emotional and psychosocial profile, job satisfaction and risk stressors. The second questionnaire applied was the Lipp Adult Stress Symptom Inventory (ISSL), whose objective was to identify subjects with stress, the most frequent type of symptoms (physical or psychological) and the stage of stress in which they were, taking into account the stages of alertness, resistance, exhaustion. The analysis of the data revealed that 32.4% of the police interviewed are in some stage of stress, and also that the main stress and risk factor is the police work itself, that women are more affected by the stresses, like police officers working in the administrative, the most frequent symptoms of stress are insomnia, irritability, fatigue, among others. It was also verified that stress affects individuals of different age groups, mostly married (46.5%), with son (60.3%), with higher level (55.2%), 63.8% of individuals with (60.3%), have leisure activity (58.6%), 91.3% do not use any type of medication, perform their functions solely in the Military Police ( 84.5%), working in cooperation between 01 to 10 years (37.9%), feel partially accomplished professionally (65.5%), at the same time 51.7% point to dissatisfaction with salary. It is considered from this research that there is a crying urgency of the institutions to offer greater support to the military policemen who are in permanent risk situation, so that they are more recognized, valued and accepted in their demands of mental health.